2019
DOI: 10.1007/s11738-019-2959-x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of the root system: a noninvasive approach to study plant stress responses

Abstract: A pot experiment was designed to demonstrate that the parallel, single-frequency detection of electrical capacitance (C R), impedance phase angle (Φ R), and electrical conductance (G R) in root-substrate systems was an adequate method for monitoring root growth and some aspects of stress response in situ. The wheat cultivars 'Hombar' and 'TC33' were grown in a rhyolite-vermiculite mixture under control, and low, medium, and high alkaline (Na 2 CO 3) conditions with regular measurement of electrical parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The injury of the cellular membrane was proven by the increased electrolyte leakage of the needles and stems from drought stress, as reported earlier [41,42]. Membrane stability index (MSI) of roots reflecting the electrolyte leakage also supported EIS results [32]. Due to its close relationship with the membrane injury by frost stress, r e was often used to estimate semi-lethal temperatures after freezing treatments, i.e., cold hardiness of conifer trees [43,44].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The injury of the cellular membrane was proven by the increased electrolyte leakage of the needles and stems from drought stress, as reported earlier [41,42]. Membrane stability index (MSI) of roots reflecting the electrolyte leakage also supported EIS results [32]. Due to its close relationship with the membrane injury by frost stress, r e was often used to estimate semi-lethal temperatures after freezing treatments, i.e., cold hardiness of conifer trees [43,44].…”
Section: Discussionmentioning
confidence: 54%
“…It has also been applied to evaluate growth of intact root system of herbaceous plants [27], tree roots [28,29] and the mycorrhiza colonization [30], as well as the frost damages of roots in small tree seedlings [31]. Recently, single-frequency impedance measurement was used to study plant response to alkaline stress [32]. Although the application of EIS in studying drought stress was not addressed before, the following studies showed that water content of organs was associated with the magnitude of EIS parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Plant tissue acts as a capacitor when electric current passes through it, this tissue has an electrical capacitance (Cseresnyés et al, 2019;Postic and Doussan, 2016). The magnitude of this electrical capacitance can be measured in physical units -micro-and nanofarads.…”
Section: Theorymentioning
confidence: 99%
“…In medical field, EIS has proven to be valuable for diagnosing diseases, monitoring physiological changes (Gamal et al ., 2018). In agronomic field, EIS has been used for measuring soil moisture (Liu et al ., 2021b), plant growth (Repo et al ., 2005; Cseresnyes et al ., 2019), and fruit ripeness (Li et al ., 2019; Ibba et al ., 2020). In the field of food quality control, EIS can effectively assess the freshness (Perez‐Esteve et al ., 2014), water content (Yang et al ., 2013; Wei et al ., 2017), salt content (Ma et al ., 2016; Chen et al ., 2017; Schivazappa et al ., 2017), and fat content (Afonso et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%